Flash Vacuum Expansion of Maradol Papaya (Carica papaya L.) for Producing an Antioxidant-Potential Dairy Beverage Fermented by Limosilactobacillus fermentum J24 - Jesús Ayala Zavala; Teresita de Jesús Castillo Romero; José Isidro Méndez Romero; Lourdes Santiago López; Aarón Fernando González Córdova; Adrián Hernández Mendoza; Belinda Vallejo Cordoba; Manuel Vargas Ortiz (Beverages)
This study aimed to evaluate the fermentative capacity of the strain Limosilactobacillus fermentum J24 in a dairy beverage with papaya puree obtained through the flash vacuum expansion (FVE) process. Changes in phenolic content and antioxidant capacity during fermentation were investigated. Results showed that the dairy beverage with the control puree exhibited higher microbial growth than the FVE puree. Phenolic content increased during fermentation in both formulations. However, the antioxidant capacity was higher in the dairy beverage with control puree. A Pearson correlation analysis revealed a strong positive correlation between microbial load and antioxidant properties in the dairy beverage with control puree. In conclusion, the control puree promoted a higher growth of Limosilactobacillus fermentum J24 and better antioxidant properties in the papaya dairy beverage. These findings lay the groundwork for developing a potential functional dairy beverage based on papaya, effectively utilizing the fruit, reducing pollution, and adding value. This study also opens avenues for further research and development in functional dairy beverages, particularly those incorporating fruit-based ingredients.